The Relationship Between Mothers' Knowledge Level About Exclusive Breastfeeding and the Incidence of Stunting in Children Aged 24-59 Months - Permana, Irman; Norviatin, Dini; Arumtara, Hasna Nuha (Newinera Publisher, 2024)
Children under five years-old (toddlers) were very vulnerable to nutritional deficits and one of the most common was stunting. Indonesia has the third highest prevalence in Southeast Asia. Stunting incidence often occurs in toddlers aged 24-59 months with one of the risk factors, namely unbalanced food intake, including not giving exclusive breastfeeding. Lack of maternal knowledge can cause poor parenting, especially exclusive breastfeeding. The aim of the study was to discovered the relationship between maternal knowledge and exclusive breastfeeding with the incidence of stunting in toddlers aged 24-59 months in work area of Kersana Public Health Center, Brebes Regency. This study used an observational analytic approach with sectional cross design. The number of research samples used in this study was 85 selective people with a technique of concecutive sampling. Data was taken using questionnaire and the analytical technique used Spearman correlation test. Most of respondents were aged 31-40 years (53,7%), elementary school education level (47,1%), maternal status (82,4%), and who had daughters (56,5%). The results of the Spearman correlation test showed that there was a significant relationship between the maternal knowledge (p = 0.000, r = -0.886), and exclusive breastfeeding (p = 0.000, r = -0.661) with the incidence of stuntin. The study concluded that there was a significant relationship between maternal knowledge and exclusive breastfeeding with the incidence of stunting in toddlers aged 24-59 months in work area of Kersana Public Health Center, Brebes Regency, with a negative correlation direction.